Differentiation of Pseudomonas syringae pathovars originating from stone fruits - Gašić, Katarina Miodrag; Prokić, Anđelka; Ivanović, Milan; Kuzmanović, Nemanja; Obradović, Aleksa (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
Due to overlapping host range, similar symptomatology, and many characteristics they have in common, Pseudomonas syringae pathovars originating from stone fruits can easily be misidentified. In order to select tests for a rapid and efficient differentiation of P. s. pvs. syringae, morsprunorum and persicae, we studied suitability and differentiating potential of some standard bacteriological and molecular methods. Differentiation of the strains was performed using LOPAT, GATTa and ice nucleation test, nutrient sucrose broth growth and utilization of various carbon sources. PCR method provided detection of toxin-producing genes: syrB and syrD in P. s. pv. syringae, and cfl gene in P. s. pv. morsprunorum race 1. Syringomycin production by pv. siringae was confirmed in bioassay using Geotrichum candidum, Saccharomyces cerevisiae and Rhodotorula pilimanae as indicator organisms. Pathogenicity test on lemon and immature nectarine fruits, as well as on string bean pods, showed different intensity of reaction of inoculated material which could separate pv. syringae from the other two pathovars. PCR based repetitive sequences, Rep-PCR with REP, ERIC and BOX primers revealed different genetic profiles within P. syringae pathovars.
Keywords: Identification; Stone fruits; PCR; Pseudomonas syringae